Abnormal Glucose Tolerance Is Associated with a Reduced Myocardial Metabolic Flexibility in Patients with Dilated Cardiomyopathy. (21st December 2015) - Tricò, Domenico; Baldi, Simona; Frascerra, Silvia; Venturi, Elena; Marraccini, Paolo; Neglia, Danilo; Natali, Andrea
Abstract : Dilated cardiomyopathy (DCM) is characterized by a metabolic shift from fat to carbohydrates and failure to increase myocardial glucose uptake in response to workload increments. We verified whether this pattern is influenced by an abnormal glucose tolerance (AGT). In 10 patients with DCM, 5 with normal glucose tolerance (DCM-NGT) and 5 with AGT (DCM-AGT), and 5 non-DCM subjects with AGT (N-AGT), we measured coronary blood flow and arteriovenous differences of oxygen and metabolites during Rest, Pacing (at 130 b/min), and Recovery . Myocardial lactate exchange and oleate oxidation were also measured. At Rest, DCM patients showed a reduced nonesterified fatty acids (NEFA) myocardial uptake, while glucose utilization increased only in DCM-AGT. In response to Pacing, glucose uptake promptly rose in N-AGT (from 72 ± 21 to 234 ± 73 nmol/min/g, p < 0.05 ), did not change in DCM-AGT, and slowly increased in DCM-NGT. DCM-AGT sustained the extra workload by increasing NEFA oxidation (from 1.3 ± 0.2 to 2.9 ± 0.1 μ mol/min/gO2 equivalents, p < 0.05 ), while DCM-NGT showed a delayed increase in glucose uptake. Substrate oxidation rates paralleled the metabolites data. The presence of AGT in patients with DCM exacerbates both the shift from fat to carbohydrates in resting myocardial metabolism and the reduced myocardial metabolic flexibility in response to an increased workload. This trial is registered with ClinicalTrial.govNCT02440217 .